Isolation of lupenone (18-Lupen-3-one) from Roscoea purpurea root extract - Kaur, G; Gupta, V; Bansal, P; Kumar, S; Rawal, RK; Singhal, RG (Bangladesh Journal of Medical Science, 2020)
Background: Endangered plant “Kakoli” is important component of Ashtwarga group of plants and anti-aging Ayurvedic preparations. Due to limited supply of original plant, official substitutes and common adulterants are being used by drug manufacturers. There is a need to identify a marker compound that could differentiate original plant from substitutes and common adulterants. Objective: To isolate and characterize the marker compound from roots of this plant. Material and methods: The extract of plant root was prepared in methanol and marker compound was isolated from methanol extract through column chromatography by using silica gel (60–120 mesh size) in glass column (1000mm x 50mm). The compound was obtained in fractions numbered 990-1550 and isolated by cutting and pooling of TLC plate of compound having Rf = 0.52 by the use of mobile phase toluene: ethyl acetate: formic acid (9.5: 0.5: 0.1 v/v/v). Compound was characterized by using IR, NMR, Mass and UV spectroscopy. Results: The methanol extract was blackish brown in color and showed the presence of alkaloids, terpenoids, phytosterols, flavonoids, phenolics and amino acid. The isolated compound was found to be colorless terpenoid needle with m.p. 168-171°C; [α]D +62.8° (c 1.0,CHCl3). Spectral analysis confirmed presence of lupenone. Conclusion: In present study lupenone was isolated for the first time from Kakoli. None of adulterants and substitutes of Kakoli are reported to have lupenone hence can be used as marker for identification as well as differentiation of the plant from official substitutes and common adulterants. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.692-696